New Trends in Emission Control in the European Union - Merkisz, Jerzy; Pielecha, Jacek; Radzimirski, Stanisław (Springer Tracts on Transportation and Traffic, 2014)
This book discusses recent changes in the European legislation for exhaust emissions from motor vehicles. It starts with a comprehensive explanation of both the structure and range of applicability of new regulations, such as Euro 5 and Euro 6 for light-duty vehicles and Euro VI for heavy-duty vehicles. Then it introduces the most important issues in in-service conformity and conformity of production for vehicles, describing the latest procedures for performing exhaust emissions tests under both bench and operating conditions. Subsequently, it reports on portable emission measurement systems (PEMS) and their application for assessing the emissions of gaseous and particulate matter alike, under actual operating conditions and in all transport modes. Lastly, the book presents selected findings from exhaust emissions research on engines for a variety of transport vehicles, such as light-duty and heavy-duty vehicles, as well as non-road vehicles, which include farm tractors, groundwork and forest machinery, diesel locomotives, high-rail vehicles, combat vehicles and special-purpose vehicles. This work offers a valuable reference guide for researchers and professionals dealing with environmental regulations and vehicle manufacturing in the European Union.